Medical Advertising as a Polycode Text Genre - N. M. Dugalich (Ученые записки Казанского университета: Серия Гуманитарные науки, 2024)
This article explores the key features of contemporary medical print advertising in Russia, such as the subject matter, the interplay between words and images, expressive means and their frequency, as well as linguistic and visual indicators associated with medical discourse. A total of 103 Russian medical print advertisements were collected from the Internet by continuous sampling. The analysis of these advertisements confirmed that medical advertising is a form of medical discourse that has specific features. Some of them include the use of medical terms (colloquial rather than nosological), precedent phenomena, and language play. It was also found that medical print advertising relies heavily on the integrative and image-centric connections between the verbal and visual series of a polycode text.